Designing and developing an interactive projection mapping AR book on cultural heritage of Myanmar - Chan, Z. H. Ave *; Lee, Yunli * (2019)
The projection mapping technology is used to design and develop an Augmented Reality (AR) based book of the cultural heritage of Myanmar. The proposed interactive AR book contains 18 pages designed using Adobe InDesign to introduce the culture and heritage of Myanmar including the World largest book, traditional musical instruments, and various Myanmar delicacies and cuisine. Leap Motion device and VVVV toolkit are used to design and develop the AR contents which ultimately blends the virtual contents to the real world.